The artistic construction of the contemporary short Hebrew story: "Deborah Baron stories" as an example - abood Rheama, Majeed (Al-Adab Journal, 2021)
This research sheds light on the "artistic construction of the contemporary short Hebrew story", stories of Deborah Baron as a model. Initially, we defined the story in general and the short story as an independent literary genre. Then, he learned about the emergence and development of the contemporary Hebrew story. The Hebrew writers derived this literary genre from world literature, and began writing Hebrew stories along the lines of the foundations and artistic elements of the products of Western writers.In order to enrich the subject of my research, I studied two Hebrew stories of the storytelling Deborah Baron, which is (dreams) and (rays), and these stories involve under what is called the real story.Most of Deborah Baron's stories revolve around the lives of Jews in the Jewish town of Eastern Europe. This focus is due to her being from a literary generation: Asher Parach, Dov Kamehy and Aharon Kapak. And that most of her stories are echoes and testimonies about the Jewish past in the European town, and since sadness is the characteristic of her stories, and this sadness is used by the writer Deborah Baron to reveal through it the darkness of life the Jews lived in the European town. Through our reading of her stories, most of her story subjects revolve mostly around topics that concern women primarily, which is a truism because writer Baron is a woman who cares about the problems of her gender. Deborah Baron is the short story artist who carries within it a great creative material, her speech is moderate, thoughtful, and balanced, easy and clear, in which he notes the concern for the tone and rhythm for the unity of the material.Accordingly, I highlighted her biography, as I try to shed light on the technical construction in her stories on the subject of research and on the most important linguistic phenomena that characterized her linguistic style. These stories represent a bright spot in the history of contemporary Hebrew fiction